Preparation and Characterization of Phthalic Acid-Propane-1, 2-Diol-Glycerol Co-Polyester as A Biodegradable Polymer - Islam, Saiful; Haque, Moinul; Bakr, Abu (Journal of Composites and Biodegradable Polymers, 2014)
Phthalic acid propane-1,2 diol-glycerol co-polyester (PPGC) is synthesized from phthalic acid and propane-1, 2-diol with 5% glycerol of total weight as a crosslinking agent using Dean-Stark apparatus with Ferric Chloride (Approximately 0.4% of the total weight) as catalyst and o-xylene as the reaction medium at temperature 137-141° C for about 5 hours. The co-polyester is characterized by its molecular weight, elemental analysis, solubility tests in common organic solvents, swelling behavior in water and ethanol, melting point, density, pH test, IR-spectra and degradation test. Its probable structure is assigned. Molecular weight is determined by end group analysis and viscosity method. The degradation study of the co-polyester is carried out in different solutions of pH values 1.70 - 9.16. At room temperature (30°C) the co-polyester remained intact in the acid solutions (1.70 - 5.80 pH) but degraded in basic solutions (7.14 - 9.16 pH). In normal soil, it is almost 100% degradable within 60 days.